Cost-Effective Trap qPCR Approach to Evaluate Telomerase Activity: an Important Tool for Aging, Cancer, and Chronic Disease Research (Clinics, 2021)
OBJECTIVES: Telomeres are a terminal ‘‘DNA cap’’ that prevent chromosomal fusion and degradation. However, aging is inherent to life, and so is the loss of terminal sequences. Telomerase is a specialized reverse transcriptase encoded by self-splicing introns that counteract chromosome erosion. Telomerase activity is observed during early embryonic development, but after the blastocyst stage, the expression of telomerase reduces. The consequences of either insufficient or unrestrained telomerase activity underscore the importance of ongoing studies aimed at elucidating the regulation of telomerase activity in humans. In the present study, we aimed to standardize a simplified telomerase repeat-amplification protocol (TRAP) assay to detect telomerase activity in unstimulated and PHA-stimulated mononuclear cells. METHODS and RESULTS: Our optimized qPCR-based can efficiently evaluate telomerase activity. Quantification of protein and DNA between unstimulated and PHA-stimulated peripheral blood mononuclear cells revealed cellular activation and cell-cycle entry. The assay also showed that relative telomerase activity is significantly different between these two conditions, supporting the applicability of the assay. Furthermore, our findings corroborated that telomerase activity decreases with age. CONCLUSIONS: Telomeres and telomerase are implicated in aging and development of chronic diseases and cancer; however, difficulty in accessing commercial kits to investigate these aspects is a critical constraint in health surveillance studies. Our optimized assay was successfully used to differentiate telomerase activity between unstimulated and stimulated cells, clearly showing the reactivation of telomerase upon cell activation. This assay is affordable, reproducible, and can be executed in resource-limited settings.